Performance Analysis of ‘Narmada Nidhi’ Poultry Under Backyard Farming System in Mandla District of Madhya Pradesh - Yadav, J. S.; Mandal, M. K.; Singh, R.; Baghel, R.P.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Backyard poultry farming (BYPF) is an important activity to empower tribal women socially and economically, as it generates cash income and provides employment opportunities, while increasing production of valuable foods (eggs and meat) that improve household nutrition. The present study was conducted in six villages of Narayanganj and Niwas blocks of Mandla District. Data were collected through a structured interview schedule by personal interview method. After proper extension interventions, six self-help-groups were formed and each group was provided with 50, (eight weeks age growing) Narmada Nidhi chicken to analyse its performance parameter under backyard system. The study shows that, average age and weight at sexual maturity obtained in this study were 160.5±3.60 days and 1415±10.12 g, respectively. The annual average egg production obtained was 165.27 ± 3.15 eggs/hen/year. The mean value egg weight, egg length and egg width was 48.67 ± 2.92 g, 51.91 ± 1.02 mm and 40.32 ± 3.01 mm, respectively while the yolk weight, albumen weight, shell weight, shell thickness and yolk color were 16.43 ± 1.78 g, 25.76 ± 2.67 g, 5.87 ± 0.94 g, 0.42 ± 0.08 mm and 6.01 ± 3.98, respectively.